ANALISIS BERPIKIR KRITIS SISWA MELALUI INFOGRAFIS MATERI PERUMUSAN PANCASILA DI SMK PGRI 1 KUDUS - Chusna, Vaza Anil; Sutono, Agus; Sudrajat, Rahmat (FPIPSKR Universitas PGRI Semarang, 2026)
This study investigates the prevalent issue of underdeveloped critical thinking skills among vocational students at SMK PGRI 1 Kudus, a context in which fervor for specialized majors often eclipses engagement with general subjects. The research objective is to enhance critical thinking competencies within class X MPLB 3 by implementing infographic media centered on the historical formulation of Pancasila. Employing a descriptive qualitative methodology, the findings indicate that fostering critical thinking is essential for empowering students to articulate their viewpoints effectively in an academic setting. The integration of infographic learning media demonstrably and significantly augments students' critical thinking capacities. The study concludes by advocating for pedagogical approaches wherein educators proactively encourage students to voice their perspectives, thereby cultivating a more dynamic, interactive, and intellectually rigorous learning environment.